The Potential of Phytotherapy In Managing Dyspepsia: A Narrative Review - Pratidina, Malfa Laila; Levita, Jutti (Universitas Pakuan, 2023)
Dyspepsia, commonly known as indigestion, is delineated as suffering the manifestations of epigastric pain, nausea, burning, or after-meal fullness. The common therapy for dyspepsia, e.g., proton pump inhibitors or histamine-H2 receptor antagonists, has shown some adverse effects, thus, phytotherapy is currently becoming the drug of interest. Phytotherapy, additionally known as herbal medicine or botanical medicinal drug, includes the use of plant-derived compounds to prevent, alleviate, or therapy for diverse ailments. Most medications commonly used in Chinese traditional medicine or Asian folklore drugs contain mixtures of several plant extracts. Twelve clinical trials reported the effect and safety of phytotherapy on gastrointestinal disorders. Taken together, phytotherapy may be considered safe for the management of dyspepsia with close monitoring of the dose and duration of therapy.